(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article focuses on the possibilities of developing the thinking of undergraduates in the process of teaching piano music common and different aspects of melodious features, serve to illuminate the scientific and theoretical importance of musical genres.